Evaluation of an oral health education training program for kindergarten teachers - Joanna Cheuk Yan Hui; Joanna Cheuk Yan Hui; Chun Hung Chu; Jieyi Chen; Jieyi Chen (Frontiers in Oral Health)
ObjectivesThis study aims to examine kindergarten teachers’ satisfaction and their perceived impact of an oral health education (OHE) training program.MethodsThis study followed the steps outlined in the Program Evaluation Standards in Public Health recommended by the Centers for Disease Control and Prevention. All kindergarten teachers in Hong Kong were invited to attend the OHE training. The training comprised a lecture and a group discussion among six to eight teachers facilitated by trained dentists. The participating teachers were invited to complete an online questionnaire after the training. The questionnaire consisted of seven questions: six close-ended questions to evaluate teachers’ satisfaction with the training, their perceived oral-health-related knowledge, and their perceived competence in delivering OHE, and one open-ended question to collect their comments and suggestions for enhancing the OHE training.ResultsA total of 6,210 teachers joined the OHE training and 4,882 teachers completed the questionnaires (response rate: 79%). The survey found that 4,691 (96%) teachers were satisfied with the training, and the same number agreed that the OHE training was essential for delivering OHE. In addition, 4,680 (96%) teachers found the lecture informative and 4,393 (90%) teachers rated the group discussion as useful. After the OHE training, 4,716 (96%) teachers reported that they were more knowledgeable in recognizing childhood oral diseases and 4,665 (96%) teachers believed they were more skillful in delivering OHE. Regarding comments and suggestions, teachers opined that the OHE was informative and comprehensive. They suggested developing videos and hands-on workshops for the OHE training and expressed a desire to learn more about the dental treatment of common dental diseases. They also recommended providing teaching aids, such as booklets and tooth models, for use in kindergartens.ConclusionThe kindergarten teachers generally had a better understanding of childhood oral conditions after the OHE training. They were generally satisfied with the training and became more confident in delivering OHE to kindergarten children.